2022
DOI: 10.1080/14756366.2022.2135511
|View full text |Cite
|
Sign up to set email alerts
|

Binding selectivity-dependent molecular mechanism of inhibitors towards CDK2 and CDK6 investigated by multiple short molecular dynamics and free energy landscapes

Abstract: Understanding selectivity-dependent molecular mechanism of inhibitors towards CDK2 over CDK6 is prominent for improving drug design towards the CDK family. Multiple short molecular dynamics (MD) simulations combined with MM-GBSA approach are adopted to investigate molecular mechanism on binding selectivity of inhibitors X64, X3A, and 4 AU to CDK2 and CDK6. The RMSF analysis and calculations of molecular surface areas indicate that local structural and global flexibility of CDK6 are stronger than that of CDK2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 101 publications
2
5
0
Order By: Relevance
“…However, in the last 200 ns of the simulation, hydrogen bonds were mainly formed with H100 for 80.27% occupancy ( Supplementary Figure S13 ). The formation of these two hydrogen bonds, which formed between abemaciclib and the hinge loop of CDK6, was consistent with the results of experimental and theoretical studies ( Yuan et al, 2021 ; Chen et al, 2022 ; Sokolsky et al, 2022 ; Wang et al, 2023 ). In addition, the hydrogen bond between the atom N4 of abemaciclib and the NZ atom of K43 was not unstable from the occupancy with 22.07% for the 500 ns simulation and 20.74% for the last 200 ns simulation, respectively.…”
Section: Resultssupporting
confidence: 89%
“…However, in the last 200 ns of the simulation, hydrogen bonds were mainly formed with H100 for 80.27% occupancy ( Supplementary Figure S13 ). The formation of these two hydrogen bonds, which formed between abemaciclib and the hinge loop of CDK6, was consistent with the results of experimental and theoretical studies ( Yuan et al, 2021 ; Chen et al, 2022 ; Sokolsky et al, 2022 ; Wang et al, 2023 ). In addition, the hydrogen bond between the atom N4 of abemaciclib and the NZ atom of K43 was not unstable from the occupancy with 22.07% for the 500 ns simulation and 20.74% for the last 200 ns simulation, respectively.…”
Section: Resultssupporting
confidence: 89%
“…In the current study, in order to illustrate the selective mechanism of BRD9 and TAF1(2), three small-molecule inhibitors, 67B, 67C, and 69G, were chosen to determine their binding selectivity for BRD9 and TAF1(2) by performing MSMD simulations and binding free energy computations. Encouragingly, MSMD simulations can extract more rational conformational sampling than cMD simulations, which has been verified in previous works [ 59 , 60 , 61 ]. Furthermore, principal component analysis (PCA) [ 62 , 63 ], dynamics cross-correlation maps (DCCMs), and free energy landscapes (FELs) were combined to investigate the conformational variations and internal dynamics of BRD9 and TAF1(2) caused by inhibitor associations.…”
Section: Introductionsupporting
confidence: 67%
“…For instance, a study has demonstrated that understanding the binding selectivity of inhibitors towards CDK2 as opposed to CDK6 is important for enhancing drug design. [5] Similarly, the binding specificity of inhibitors to CDK5 is also a significant area of research, particularly in the context of neuropathological disorders such as Alzheimer's disease. [6] The role of the tubulin-associated unit (tau) protein in the neurodegenerative process is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of drug design, the binding specificity of inhibitors is a crucial aspect. For instance, a study has demonstrated that understanding the binding selectivity of inhibitors towards CDK2 as opposed to CDK6 is important for enhancing drug design [5] . Similarly, the binding specificity of inhibitors to CDK5 is also a significant area of research, particularly in the context of neuropathological disorders such as Alzheimer's disease [6] …”
Section: Introductionmentioning
confidence: 99%